Topography-driven isolation, speciation and a global increase of endemism with elevation - Steinbauer, Manuel J.; Field, Richard; Grytnes, John Arvid; Trigas, Panayiotis; Ah-Peng, Claudine; Attore, Fabio; Birks, H. John B.; Borges, Paulo A.V.; Cardoso, Pedro; Chou, Chang-Hung; De Sanctis, Michele (Wiley, 2016)
Aim: Higher-elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness.